On the Pore Size Distributions and Fractal Dimensions of Activated Carbons Evaluated on the Basis of the Analysis of Nitrogen, Argon and Benzene Vapour Adsorption Data - B.J. Trznadel; A. Światkowski (Adsorption Science & Technology)
The Dubinin–Stoeckli equation and the Horvath–Kawazoe equation have been used for the determination of the pore size distribution (PSD) for three fractions of activated carbon separated by elutriation due to their different degrees of activation (burn-off). A comparison of the PSD functions on the basis of nitrogen, argon and benzene adsorption isotherms has been undertaken. The general form of the Dubinin–Stoeckli equation has been developed for nitrogen and argon as an adsorbate. For all adsorbates studied, correction factors including adsorption in mesopores were introduced. New formulae for this correction factor have been proposed for nitrogen and argon. Quantitative evaluations of PSD functions for these three different adsorbates lead to the conclusion that it is possible to use the benzene isotherm as well as the nitrogen or argon isotherms to characterise the microporous structure of the adsorbent. Comparison of the porous structure parameters was extended by a fractal analysis.